2013
DOI: 10.1016/j.neubiorev.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Veridical mapping in the development of exceptional autistic abilities

Abstract: Superior perception, peaks of ability, and savant skills are often observed in the autistic phenotype. The enhanced perceptual functioning model (Mottron et al., 2006a) emphasizes the increased role and autonomy of perceptual information processing in autistic cognition. Autistic abilities also involve enhanced pattern detection, which may develop through veridical mapping across isomorphic perceptual and non-perceptual structures (Mottron et al., 2009). In this paper, we elaborate veridical mapping as a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 233 publications
11
168
1
7
Order By: Relevance
“…Veridical mapping and hypersystemizing may themselves emerge from other traits tied to autism, which are sensory hypersensitivity, excellent attention to detail and superior lowlevel perceptual abilities Mottron et al, 2006). Importantly, Mottron, Dawson and Soulières (2009;also Bouvet at al., 2014;Mottron et al, 2013) have hypothesised that veridical mapping may motivate savant syndrome, and may independently motivate synaesthesia. For example, Mottron et al (2013) suggest that the savant skill of hyperlexia (precocious reading ability) depends on veridical mapping across language systems: i.e., detecting patterns between the written system of graphemes and the spoken system of phonemes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veridical mapping and hypersystemizing may themselves emerge from other traits tied to autism, which are sensory hypersensitivity, excellent attention to detail and superior lowlevel perceptual abilities Mottron et al, 2006). Importantly, Mottron, Dawson and Soulières (2009;also Bouvet at al., 2014;Mottron et al, 2013) have hypothesised that veridical mapping may motivate savant syndrome, and may independently motivate synaesthesia. For example, Mottron et al (2013) suggest that the savant skill of hyperlexia (precocious reading ability) depends on veridical mapping across language systems: i.e., detecting patterns between the written system of graphemes and the spoken system of phonemes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Mottron, Dawson and Soulières (2009;also Bouvet at al., 2014;Mottron et al, 2013) have hypothesised that veridical mapping may motivate savant syndrome, and may independently motivate synaesthesia. For example, Mottron et al (2013) suggest that the savant skill of hyperlexia (precocious reading ability) depends on veridical mapping across language systems: i.e., detecting patterns between the written system of graphemes and the spoken system of phonemes. Mottron et al (2013) suggest that veridical mapping might also encourage grapheme-colour synaesthesia, in which relationships between graphemes (e.g., the low to high frequency of graphemes in English) are known to be mapped onto relationships between colours (the low to high frequency of colour-terms in English; see Simner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…By setting precision invariably high, ''training examples" will be more literally encoded (cf. veridical mapping, Mottron et al, 2013). According to HIPPEA, inefficient predictive updating will result in different top-down priors or predictions, namely overfitted, low-level ones that capture too much redundant inputs, and possibly an impoverished set of very high level ones that are not sufficiently informative.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research using event-related potentials (ERP) also revealed enhanced neural detection of frequency changes in ASD at the pre-attentive level (using mismatch negativity or MMN) (e.g., Ferri et al 2003;Gomot et al 2002;Kujala et al 2007; but see Jansson-Verkasalo et al 2003; see Haesen et al 2011 for an extensive recent review of the psychophysical and electrophysiological literature on auditory processing in ASD). Relevant is also the increased prevalence of absolute pitch and musical savants in the ASD population (e.g., DePape et al 2012;Heaton et al 2008a, b, c;Miller 1989;Mottron et al 2013) and the increased prevalence of autistic traits among possessors of absolute pitch (e.g., Dohn et al 2012). The occurrence of this superior pitch processing contrasts with the inferior temporal processing abilities in ASD (such as impaired gap-in-noise detection, duration discrimination, temporalenvelope processing, temporal order judgement; e.g., Alcántara et al 2012;Bhatara et al 2013;Kwakye et al 2011;Lepisto et al 2005Lepisto et al , 2006Samson et al 2011; but see Jones et al 2009;Kasai et al 2005) and the evidence of speech perception impairments (Alcántara et al 2004;Bhatara et al 2013;Groen et al 2009) and generally delayed speech and language development (e.g., Anderson et al 2007).…”
Section: Introductionmentioning
confidence: 99%